2000
DOI: 10.1002/(sici)1098-1004(200005)15:5<463::aid-humu8>3.3.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a simple and rapid single-strand conformation analysis for detection of mutations in the PROS1 gene: Identification of seven novel mutations and three novel, apparently neutral, variants

Abstract: Anticoagulant protein S (PS) deficiency is a known risk factor for thrombophilia. The structure and high allelic heterogeneity of the PS gene (PROS1), together with the presence of a 97% homologous pseudogene, complicates PROS1 analysis. We have optimized a simple, fast, and non-isotopic Single-Strand Conformation Analysis (SSCA or SSCP) method for PROS1 mutation detection. This is accomplished through the analysis of the single-stranded and heteroduplex DNA fragments corresponding to 15 PCR segments that incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 32 publications
3
28
0
Order By: Relevance
“…It has been suggested that they are phenotypic variants of the same genetic disorder, as both phenotypes were found to coexist in the same families. 123,148,[155][156][157] In one of these families, deficient individuals were subsequently found to carry the same causative mutation, and the change in phenotype (type I to type III) was shown to be due to an age-related increase in TPS levels. 140 The mutation present in this family (Gly295Val) was later shown to completely abrogate PS expression from the affected allele.…”
Section: Type I and Type Iii Ps Deficienciesmentioning
confidence: 99%
“…It has been suggested that they are phenotypic variants of the same genetic disorder, as both phenotypes were found to coexist in the same families. 123,148,[155][156][157] In one of these families, deficient individuals were subsequently found to carry the same causative mutation, and the change in phenotype (type I to type III) was shown to be due to an age-related increase in TPS levels. 140 The mutation present in this family (Gly295Val) was later shown to completely abrogate PS expression from the affected allele.…”
Section: Type I and Type Iii Ps Deficienciesmentioning
confidence: 99%
“…Some intronic splice variants (Choi et al , 2011; Menezes et al , 2017; Wang et al , 2019) and structural variants (Hurtado et al , 2009; Lind-Halldén et al , 2012; Seo et al , 2014) have also been reported. Note that, compared to exonic variations, very few variations have been described in the promoter region of the PROS1 gene (Espinosa-Parrilla et al , 2000; Hurtado et al , 2008; Li et al , 2019; Sanda et al , 2007; Tang et al , 2013) and even fewer have been functionally characterized. To our knowledge, the c.-168C>T is the sole PROS1 promoter variation that has been experimentally demonstrated to cause inherited PSD by affecting the core binding site of Sp1 transcription factor (Sanda et al , 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, screening for PROS1 gene mutations has been performed in a number of studies. The proportion of cases where no mutations are detected varies widely between studies [10,17,[23][24][25][26][27][28][29][30][31][32][33]. When all cases are pooled together, PROS1 gene mutations are not detected in 47% of PS deficient families.…”
Section: Introductionmentioning
confidence: 99%